Generic Science Skills with Student Learning Perseverance in Junior High Schools in Science Learning - Yusnidar; Haryanto; Kamid; Darmaji; Kurniawan, Dwi Agus; Nawahdani, Ahmad Mansur (Jurnal Ilmiah Pendidikan dan Pembelajaran, 2024)
Although Natural Science (IPA) has become an integral part of the curriculum at the junior high school level, there are several gaps in learning practices in the field that need attention. One of the main gaps is related to applying generic science skills in the teaching-learning process. This study investigates the relationship and influence between science generic skills and the perseverance of junior high school students in learning science. This study belongs to the quantitative research category that uses descriptive and inferential statistical analysis methods with Pearson correlation and Regression tests. The research sample consisted of 52 seventh-grade students at the junior high school level, selected using random sampling. The data collection methods used were observation and questionnaires. The data collection instruments included an observation sheet with a Likert scale of 4 for students' science generic skills and a questionnaire with a Likert scale 5 for students' learning perseverance. Data analysis techniques in this study used a quantitative approach consisting of descriptive and inferential statistical analysis. The findings showed a significant correlation between science generic skills and students' learning perseverance in both schools. So, it can be concluded that the higher the students' generic science skills, the higher the level of their perseverance in learning science. In addition, science generic skills influence students' learning perseverance. The implications of this study are very relevant for developing science education at the junior high school level.